Arterial stiffness is increased in healthy subjects with a positive family history of hypertension. (17th November 2015) - Liu, Jinbo; Wang, Hongyu; Zhao, Hongwei; Liu, Huan; Li, Lihong; Zhou, Yingyan
Abstract: A positive family history of hypertension is a risk factor for cardiovascular diseases. We investigated the value of pulse wave velocity (PWV) in healthy subjects with a positive family history of hypertension. 255 healthy subjects (M/F: 75/180) were divided into two groups according to without (group 1) or with (group 2) a positive family history of hypertension. Carotid-femoral pulse wave velocity (CF-PWV) was measured by Complior apparatus. Our results showed that CF-PWV was significantly higher in group 2 than in group 1 (7.90 ± 1.31 versus 7.32 ± 1.15 m/s, p  < 0.001). High-density lipoprotein cholesterol (HDL-C) was significantly higher in group 1 than in group 2. Multiple linear regressions showed that age, family history, GLU, and MAP were independent influencing factors of CF-PWV in the entire study group. Our present study showed PWV is significantly higher in healthy subjects with a positive family history of hypertension. Family history might play an important role in this process.